ENHANCING STUDENTS’ WRITING SKILL THROUGH DIGITAL STORY TELLING (DST): STUDENTS’ VOICES - Irma Savitri Sadikin; Lutfiyah Lutfiyah; Meiyanti Nurchaerani (IKIP Siliwangi, 2023)
Students in the first semester of one of private junior high schools in Jakarta were charged with actively engaging in their own learning experiences by utilizing Digital Story Telling (DST) to enhance their writing activity. A questionnaire was developed and administered to 29 students in order to get perspective regarding their personal and group experiences with the implementation of DST in the English classroom. The investigation revealed that there were enhancement of students' writing, the development of students' collaborative abilities, the improvement in students' participation in class, the formation of a pleasant learning atmosphere, and the increase in students' enthusiasm in writing. Keywords: Students’ Perception; Digital Storytelling; Teaching Writing